Potential Impact of Existing Interventions and of Antiretroviral Use in Female Sex Workers on Transmission of HIV in Burkina Faso: A Modeling Study. (1st March 2015) - Low, Andrea; Nagot, Nicolas; Konate, Issouf; Meda, Nicolas; Segondy, Michel; Van de Perre, Philippe; Mayaud, Philippe; Vickerman, Peter
Abstract : Background: The impact and cost-effectiveness of antiretroviral treatment (ART) as prevention is likely to vary depending on the local context. Burkina Faso has a concentrated mature HIV epidemic where female sex workers (FSW) are thought to have driven HIV transmission. Methods: A dynamic HIV transmission model was developed using data from the Yerelon FSW cohort in Bobo-Dioulasso and population surveys. Compared with current ART provision [status quo (SQ)], the model estimated the proportion of HIV infections averted or incremental life-years gained per additional person-year of ART over 20 years for ART targeting different subgroups or expanding eligibility to all HIV-infected individuals compared with SQ. Results: Modeling suggests that condom use within commercial sex has averted 40% of past HIV infections. Continuing SQ averts 35%–47% of new infections over 20 years compared with no ART. Expanding ART eligibility to all HIV-infected individuals and increasing recruitment (80% per year) could avert a further 65% of new infections, whereas targeting full-time FSW or all FSWs achieved less impact but was more efficient in terms of life-years gained per 100 person-years of ART. Local HIV elimination is possible with expanded ART provision to FSWs but requires condom use within commercial sex to be maintained at high levels. Conclusions: Increasing FSW recruitment onto ART could be a highly efficient method for reducing HIV transmission in concentrated epidemic settings but should not be undertaken at the expense of existing interventions for FSWs. Specialized clinics providing multiple interventions for FSWs should be a fundamental component of prevention in concentrated epidemics. Abstract : Supplemental Digital Content is Available in the Text.